REVERSIBLE ENCRYPTION AND INFORMATION HIDING - Durga Patil, Darshana Khandare (International Journal of Innovations in Engineering Research and Technology, 2022)
Lately, an increasing number of interests is paid to reversible information hiding (RDH) in encrypted pictures, because it continues the awesome property that the original picture cover may be losslessly recovered after that is embedded is extracted while protecting the photograph content’s as private. All techniques used previously embed data through reversibly vacating room from the pictures that are been encrypted, which may additionally purpose a few mistakes on records extraction and/or picture recuperation. in this paper, we advise a novel method with the aid of reserving room before encryption with a traditional RDH set of rules, and thus it will become smooth for the data hider to reversibly embed facts inside the encrypted photograph. The proposed approach can gain real reversibility, this is, and statistics extraction and image recuperation are freed from any blunders. Experiments show that this novel approach can embed large payloads for the equal image great as the formerly used strategies, along with for PSNR dB.